First International seminar on biomechanics (Fiep Bulletin - online, 2015)
At least 141 specialists coming from 22 countries took part in this Siminar which the FIEP – Bulletin  announced in its Nos. ans 2, 1967: Germany (24), England (8), Austria (3), Belgium (11) Canada (3),  Denmark (2) USA (10), Finland (1), France (3), Holland (2),  Hungary(3), Israel (2), Italy (2), Japan (3), Poland (1), Portugal (1),  Rumania (2), Sweden (4), Switzerland (34), Czechoslovakia (7), URSS (2), Yugoslavia (1).